UJI SITOTOKSISITAS SENYAWA 7-O-BENZOIL-3,4- DIMETOKSIISOFLAVON HASIL SINTESIS PADA KULTUR CELL LINE KANKER PAYUDARA MCF-7 DAN T47D - , GARNISA ARSYI AOTEAROA, Dra. Sri Herwiyanti, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Cancer is one of the main causes of death in 2008, and breast cancer is the most common cancer in females worldwide. Non-operative therapy modalities of breast cancer give great benefits, although they have many side effects and even resistency. Isoflavone, a kind of phytoestrogen, is thought to play a beneficial role in preventing breast cancer and may functions as antiestrogens/weak estrogen. Isoflavone derivates are expected to have cytotoxic activity on breast cancer cell line culture MCF-7 and T47D. Objectives: This study was intended to know the cytotoxic activity of novel substance 7-Oâbenzoylâ3,4- dimetoxyisoflavone on breast cancer cell line culture MCF-7 and T47D. Method: The cytotoxicity of the substance was tested against breast cancer cell line MCF-7 and T47D using MTT assay with serial concentration. The IC50 value was obtained using probit regression analysis. Result: The IC50 value of 7-Oâbenzoylâ3,4- dimetoxyisoflavone in cell lines MCF-7 was 150,320 Â±105,75 Âµg/mL whereas in cell lines T47D was 105,888 Âµg/ml Â±90,74. The IC50 value of doxorubicin in cell lines MCF-7 was 5,735 Â±4,79 Âµg/mL whereas in cell lines T47D was 36,763 Âµg/ml. Conclusion: Novel substance 7-O-benzoil-3,4- dimetoksiisoflavon does not have cytotoxic activity against breast cancer cell line MCF-7 and T47D.